Transforming Learning in Primary Schools: The Effectiveness of Contextual Approaches in Improving Student Motivation and Comprehension - Echa Khofifatul Ma'Rifah (Tahta Media Group, 2024)
This research is motivated by several events that show that students are less actively involved in the learning process and do not really understand the material being taught. Students who cannot understand the material being taught can cause students to be less motivated to learn. Therefore, the teacher must choose a suitable model for overcoming these problems. To respond to these problems, research is carried out which aims to increase student motivation and students' ability to understand the material. The method used in this research is qualitative research/literature study or library research, which takes reading sources from secondary data collected. The results of this study indicate that the application of contextual learning models in elementary schools can improve students' ability to understand the material because, in contextual learning, students relate the material to their surrounding environment or also the experience of students so that students can more easily gain an understanding of the material and students are also more motivated by fun learning than that students can be active in class. This study concludes that applying contextual learning models can improve students' ability to understand material through a learning process that suits students' needs.